Islamization of undergraduate medical practice: Does mobile technology play a role? - Abdul Razak, Ardilla Hanim; Goh, Kian Liang; Noor Rahin, Mohd Shahidan (The Institute of Electrical and Electronics Engineers, Inc., 2017)
Religion has always been alienated in medical education and the secular world. This has contributed to the increasing problems of uncaring doctors, quite paradoxical to the core values of medical profession of helping and healing patients. IIUM has embarked on the journey of introducing Islamic medical practice in the medical education, which has been carried out vehemently by the orthopaedic department. Following the successful implementation of this curriculum, mobile technology was garnered to create a mobile orthopaedic app, OrthoBoard, to cater to the younger generation of tech- savvy undergraduate students. This paper highlights the important role of mobile app in transforming the traditional teaching and learning methods to a modern, content-immersive and learner-centric medical education with greater emphasis on the Islamization of medical knowledge and practice.